Kajian Asuhan Keperawatan pada Tn. I dengan Gangguan Persepsi Sensori: Halusinasi Pendengaran di Ruang Sadewa RSJD Kota Surakarta - Yusuf S, Ghifrano, Arif Widodo, A.Kep., M.Kes (2015)
STUDY ON NURSING TN. I INTERFERENCE WITH sensory perception:auditory hallucinations IN WARD Sadewa RSJD SURAKARTA(Ghifrano Yusuf Satria, 2015, 48 pages) ABSTRACT Background: Based on the basic health research data showed the number of mental disorders in 2013 reached 5,6% on the number inhabitant. Based on the java city healt departement in 2012 the incidence of mental disorders ranges between 3.300-9.300 people. Based medical records RSJD Surakarta in the period of january through march 2015 as many as 4.021 patients. Methods: The authors use metodedeskripsi, as for a sample that is Mr. I, the authors obtained data derived from assessment interviews, observation, and medical records. Objective:to know the nursing care to clients with impaired sensory perception: Hallucinations include assessment, intervention, implementation and evaluation of nursing. Results: after keperawatn care for the results obtained 3x24 hours, clients can build a trusting relationship, willing to learn how to rebuke, to understand the importance of the drug to cure the disease clients, and be able to make a daily schedule to reduce the frequency of the appearance of hallucinations itself. Conclusion: cooperation among the health care team with the client / family is needed in the process of achieving a cure clients. Terapiutik communication can encourage more cooperative clients, the drug was also very instrumental in the healing process, so that every p atient must not until withdrawal.Keywords: disturbances of sensory perception, auditory, hallucinations